Nonobstructive angioscopy in patient with atherosclerotic renal artery stenosis - Komatsu, Sei (J Cardiol Cases, 2013)
Few applications of angioscopy for evaluating atherosclerosis of the abdominal aorta have been described. We report the demonstration of atherosclerotic yellow plaque by nonobstructive angioscopy in a patient with left renal artery stenosis. Computed tomography angiography showed stenosis in one of the left renal arteries in a 65-year-old man who presented with renal impairment and hypertension. Invasive selective renal angiography indicated severe stenosis in the proximal portion of the inferior left renal arteries. Intravascular ultrasound demonstrated eccentric plaque with predominant low-density plaque with calcification as the culprit. Percutaneous transluminal renal angioplasty with stent implantation of the left renal artery was performed. Nonobstructive angioscopy demonstrated a grade 3 yellow culprit plaque at the proximal end of the stent, and grade 2 and grade 1 yellow plaques as the culprit plaques at the middle and distal portions of the artery, respectively. <Learning objective: Atherosclerotic renal artery stenosis characterized by lipid-rich plaque and yellow plaque was diagnosed by intravascular imaging, such as intravascular ultrasound and angioscopy. As the stenosis was hemodynamically significant, percutaneous transluminal renal angioplasty was successfully performed. Nonobstructive angioscopy may be potentially applied for monitoring of transluminal ablation of the renal artery sympathetic nerves during drug-resistant hypertension.>